PENGARUH MEDIA PHYSICS EDUCATIONAL TECNOLOGY (PhET) TERHADAP HASIL BELAJAR PESERTA DIDIK TENTANG RANGKAIAN LISTRIK - Septianti, Andi Nurtiara; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine influence of physics educational technology (PhET) simulation media toward student learning achievement about electrical circuits in class IX SMP Negeri 24 Pontianak. The purposive samplinf technique for this study class IX A and IX C SMP Negeri 24 Pontianak. The Quasy Experimental method with nonequivalent controlgroup design was conducted on this study. Instrumen for measuring achievement about electrical circuit was peper pencil test this with 15 item essay the realiability index of this test was 0.895 and this realiability very high. Based on posttest data analysis using the t test, the value of Asyim was obtained. Sig (2-tailed) of 0.027. Those value indicate that student achievement about electrical circuit differences in learning outcomes between students who use PhET Simulation media and students who do not use PhET Simulation media. Learning using media Physics Educational Tenology Simulation (PhET) about electrical circuits in SMP Negeri 24 Pontianak has an effect of 37.08% on the improvement of student learning outcomes.Keywords: Electrical Circuits, Learning Outcomes, Physic Educational Tecnology (PhET)